Polyamines in Plant Biotechnology, Food Nutrition and Human Health - Alcázar, Rubén; Margarida Fortes, Ana; Tiburcio, Antonio F. (Frontiers Media SA, 2020)
Polyamines (PAs) are low-molecular-mass organic polycations derived from amino acids. Structurally, PAs are aliphatic chains containing two or more amine groups. In plants, the best studied PAs are the diamine putrescine (Put), the triamine spermidine (Spd) and the tetraamine spermine (Spm). Plants also produce an isomer of Spm, thermospermine (Tspm), that has an important role in vascular tissue development. Cadaverine (Cad) is another diamine that is produced from lysine, which also plays physiological roles in plants. PAs can be regarded as plant growth regulators with potential applications in agriculture and plant biotechnology. The use of chemical or genetic approaches aiming at the manipulation of endogenous PA levels has demonstrated their involvement in many aspects of plant development. These include seed germination, root development, plant architecture, in vitro plant regeneration, flowering, senescence, fruit ripening and plant responses to abiotic and biotic stresses. For example, pre-soaking seeds with PAs significantly improves seed germination and seedling performance under adverse environmental conditions. PAs also regulate plant morphology in vivo and plant organogenesis in vitro depending on the Put to Spd ratio. Spraying ornamental plants with PAs delays flower vase life and significantly improves flower quality characteristics. Pre-treatments with inhibitors of PA biosynthesis or catabolism are good approaches for delaying plant senescence, whereas genetic depletion of hypusine, a Spd derivative, also delays senescence. Elevated PA levels are one of the most remarkable metabolic hallmarks in plants exposed to drought, salinity, chilling and heat, which are the major abiotic stresses that adversely affect plant growth and productivity worldwide. Compelling evidence indicates that exogenous applications of PAs result in protective responses to damages induced by different abiotic stresses. Overexpression of several PA metabolic genes in many plant species has been shown to induce tolerance to abiotic and biotic stresses. Therefore, chemical or genetic manipulation of PA levels have practical applications in improving stress tolerance. Modulation of PA metabolism can also be used to control fruit ripening and postharvest decay, as well as to improve fruit quality traits. Dietary PAs from plant origin are considered very important for human nutrition and health because they contain relatively high amounts of Put and/or Spd, which are major sources of PAs to the body pool. Some of the health-beneficial effects of dietary PAs in humans are related to protection against oxidative stress, maintenance of gut integrity, modulation of inflammation and immune functions, among others. It is well known that PAs act in the control of relevant human pathologies including cancer, immunological, neurological and gastrointestinal diseases. In general, it seems that high PA-containing diets are beneficial for cell growth (i.e. in infants), whereas low PA-containing diets are beneficial for avoiding unwanted high rates of cell proliferation (i.e. tumor growth). This Research Topic covers both basic and applied research on PAs in plant biotechnology, food nutrition, and human health.